The Effect of Waiting Time, Accessibility, Perception of Risk, Feeling Benefit on The Intention to Reuse Halodoc App - Fahriza, Firza; Darmawan, Didit (LPPM Universitas Trunojoyo Madura, 2025)
Health services in Indonesia have undergone significant changes. Post-pandemic, health services have had to adjust to changes. Health systems around the world have faced unprecedented challenges as a result of the pandemic. The more advanced and rapid information technology and supported by the post-pandemic world that is our focus, further needs must be met with digital interaction, with the aim of making it easier for people to carry out various activities. The purpose of this study is to ascertain how patient attitude, perceived benefits, risk perception, waiting time, and accessibility affect the intention to re-use the Halodoc application. This study employs quantitative techniques. The population of this study were people who had used the Halodoc App. Researchers distributed 116 questionnaires with 103 responses. This study uses multiple linear regression analysis techniques. Based on the t test results, it shows that the value of waiting time, accessibility, perceived risk, perceived benefits have a significant effect on the intention to reuse the Halodoc App.